The Value - Fact Dichotomy: A Post-modern Perspective on the Crossroads of Religion and Science - Paul Rohan, J.C. (Sri Lanka National Seminary Journal, 2020)
Today’s world is changing at an unprecedented pace, in all the quarters of life. Today’s science is not a mere provider of the amenities of life, but has become a weltanschauung, touching and transforming all the human value system, meaning system, expectation level, etc. It is posing questions, tougher than ever before and offering opportunities, brighter than ever before. The development of science and technology has made the world a ‘Global Village’ which is no more a metaphor, but a reality in which we find ourselves in. Due to the vast social changes and the rise of materialistic trends, religions have lost their meaning. In such a situation the most impending danger to the current human society all over the world is that the traditional conceptions of values have been replaced with postmodern values which are influenced by science and which are merely facts, figures, numbers and statistics that are quantitative and accumulative. In order to bring back values to mankind, which are qualitative and meritorious, there is an urgent need to a dialogue between religion and science. Arriving at the crossroads of religion and science will make the science - religion dialogue sensible. This research speculates on the dilemmas created by the value - fact dichotomy and envisages on the need of arriving at the crossroads of religion and science for a dialogue. Such a study takes a wholistic and integral approach to the religion and science, and to values and facts.
Keywords: Dilemma; Ultimate; Uni-dimensional; Nihilism; Obligation; Weltanschauung